DETERMINACIÓN CEFALOMETRICA DE LA POSICIÓN DEL INCISIVO INFERIOR EN NIÑOS PERUANOS PORTADORES DE UNA MALOCLUSIÓN DE CLASE I. - Orellana Manrique, Oriel (1998)
The present study determines the position of the above motioned incisive in accordance with cephalometric in the maloclussion of frame class I. The sample was fit by the cephalometric radiographs of 50 children’s who assits to the Clínica Odontologica de la Facultad de Odontología de la UNMSM Cephalometric analysis were aplied of STEINER, TWEED and RICKETTS, giving a result in all cases a protussion of the inferior incisive althoug the magnitude of this protussion was not equivalent between the 3 analysis.